ANALISIS PENGARUH INVESTASI PEMERINTAH DAN SWASTA TERHADAP PENCIPTAAN KESEMPATAN KERJA DI SUMATERA UTARA - Hasibuan, Lailan Safina; Rahayu, Sri Endang (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2011)
Based on the result of research, domestic investment has a positive influence to the development industry of Medan with coefficient which means every increment 1% domestic investment, will cause the raise development industry in Medan as big as 0,001%. Also with the foreign investment has a positive influence to development of industry in Medan as big as 0,001%. Determination coefficient shows that as a whole domestic investment and foreign investment explain the influence of their relation with the development industry in Medan as big as 73,1% and the rest so much as 26,9% is explained by other statistical variable that are not include in the estimation model.